2024
DOI: 10.1021/acs.jpcc.3c07443
|View full text |Cite
|
Sign up to set email alerts
|

Improved Charge Storage Capacity of Supercapacitor Electrodes by Engineering Surfaces: The Case of Janus MXenes

Mandira Das,
Subhradip Ghosh

Abstract: Surface engineering in two-dimensional (2D) materials has turned out to be a useful technique to improve their functional properties. By designing Janus compounds MM′C in the MXene family of compounds M 2 C, where the two surfaces are constituted by two different transition metals M and M′, we have explored their potentials as electrodes in a supercapacitor with an acidic electrolyte. Using density functional theory (DFT) in conjunction with the classical solvation model, we have made an indepth analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…, stoichiometries) of MXenes considered, it was observed that: (i) Janus MXenes and MXenes with distinct surface terminations and transition metals have not yet been successful synthesized due to the difficulty of composing the bottom and top surfaces of MXenes with different elements or groups. 11,58,59 (ii) For hybrid transition metal MXenes, although there are several cases of successful synthesis, 60–62 most utilized mixed surface terminations, not considering the single element type of surface termination ( i.e. , uniform surface termination) used in the aNANt database.…”
Section: Resultsmentioning
confidence: 99%
“…, stoichiometries) of MXenes considered, it was observed that: (i) Janus MXenes and MXenes with distinct surface terminations and transition metals have not yet been successful synthesized due to the difficulty of composing the bottom and top surfaces of MXenes with different elements or groups. 11,58,59 (ii) For hybrid transition metal MXenes, although there are several cases of successful synthesis, 60–62 most utilized mixed surface terminations, not considering the single element type of surface termination ( i.e. , uniform surface termination) used in the aNANt database.…”
Section: Resultsmentioning
confidence: 99%
“…2(a) and (b)). 43,44 Accordingly, there can be four possible structural models of surface functionalised Janus MXenes: Model 1, where the functional groups occupy sites A and B; Model 2, where they occupy sites C and A; Model 3 where they occupy sites B and D and Model 4 where the sites of occupancy are C and D (Fig. 2(c) and (d)).…”
Section: Resultsmentioning
confidence: 99%